Comparative characteristics of the effectiveness of toothpastes containing calcium and fluoride - O. A. Uspenskaya; O. V. Trefilova; E. N. Levkovich (LLC "Endo Press", 2020)
Today, the market has a huge selection of oral hygiene products and items, which makes it difficult for patients to choose what they need. Despite the fact that in modern paste composition includes the various active components and additives, all the maximum effect in the prevention of dental diseases is a compound of calcium and fluoride. The article is devoted to the study of the effectiveness of toothpastes containing calcium and fluoride ions in the prevention of dental diseases. The aim was to compare the effectiveness of toothpastes with calcium and fluoride in the prevention of dental diseases. The clinical and laboratory study involved 30 people aged 18-20 years. All participants in the experiment were divided into three groups. The first group used Clinpro ™ Tooth Crème (3M ESPE) treatment and prophylactic toothpaste. The second group was assigned paste SPLAT "Active" (SPLAT COSMETICS), (1000 ppm F¯, calcium glycerophosphate). Third - Colgate "Strong teeth. Fresh breath" (Colgate-Palmolive). We studied the effect of these toothpastes on indicators of the level of oral hygiene, the CFE index, caries resistance of enamel and the mineralizing potential of the oral fluid. Clinical and laboratory research data record good cleansing properties with a high level of anticaries and remineralizing effects. The use of toothpastes, which have calcium and fluorine in their composition, can affect not only the hard tissues of the tooth, but also the composition of the oral fluid. This provides an increase in the remineralizing properties of saliva and prevents a cariogenic situation in the oral cavity.